Perencanaan Dakwah Da’i dalam Mencegah Kemerosotan Akhlak Anak di Era Digitalisasi - Zulkarnain M, Rahmad Diki; Syawaluddin, Syawaluddin (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
Planning da’i da’wah in preventing the decline of children’s morals is something that must be done in rural areas. especially in the village of Kuala Bangka where many children are preoccupied with their gadgets, which damages morals, ethics, and morals. Currently, in the era of digitalization, gadgets play a major role and influence in life so it becomes a necessity to fulfill entertainment and satisfaction in social media and so children, especially those who are restricted from playing gadgets, encounter resistance with their parents, this shows a decline. morals in children, this must be prevented by the preachers that are planning da’wah what to do in the future. The purpose of this study is to examine the planning of da’i da’wah in preventing the decline of children’s morals in the digitalization era in the village of Kuala Bangka. One of the places in North Labuhan Batu district, Kualuh Hulu sub-district, Kuala Bangka village, Pekan hamlet. Data was collected through observation and interviews with ustadz and the community in the village of Kuala Bangka. Observing and paying attention to the environment around Kuala Bangka to build a preacher’s plan to increase religious understanding and especially to improve the moral decline of children in the digitalization era. Therefore, a preacher explained how parents can set limits for their children in using gadgets, with the aim of preventing deviant behavior. There is a time limit for playing with gadgets and time for studying, bearing in mind that the time is not set by parents for children, therefore in this study, I am more directing how a da’i plans to emphasize parents to their children related to the existence of limitations in playing gadgets, worship time and studying the Koran or religion.